EXPLORING A MODERATED MEDIATION MODEL OF SITUATIONAL CONTEXT AND BRAND IMAGE ON PURCHASE INTENTION VIA ELECTRONIC WORD OF MOUTH (EWOM) A CASE STUDY OF SHOPEE IN WEST JAVA - Abdul Rahman; Mahir Pradana; Arry Widodo (PT. Jurnal Center Indonesia Publisher, 2025)
E-commerce has become one of the most dynamic industries in the digital era, and electronic word of mouth (eWOM) greatly influences consumer behaviour. Shopee, as a popular e-commerce platform in West Java, faces challenges in increasing user purchase intention, particularly with an approach based on review communication and brand image. The objective of this research is to examine how eWOM credibility, quantity, and quality impact purchase intention, with brand image as the mediating variable and situational context as the moderating variable in the study of the Shopee application in West Java. This study uses a quantitative approach with the Structural Equation Modelling-Partial Least Squares (PLS-SEM) method. Data were collected from 500 respondents who are users of the Shopee application in West Java. The research results show that eWOM quantity has the greatest influence on purchase intention, followed by brand image, which has been shown to be a significant mediator. On the other hand, eWOM credibility and quality do not have a direct impact on purchase intention. Furthermore, situational context as a moderating variable does not have a significant impact on the relationship between eWOM quantity and brand image. This study helps e-commerce businesses create better data-driven marketing strategies. To build trust and encourage customer purchasing decisions, it is important to increase the number of reviews, enhance brand reputation, and improve the quality and credibility of the reviews.